(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
In the modern context of globalization and growing environmental challenges, tourism is faced with the need to implement innovative solutions aimed at sustainable development. The development of sustainable tourism products is becoming an important tool for ensuring a balance between the interests of tourists, local populations and the natural environment. The article discusses key areas of innovation in the field of sustainable tourism, including the use of digital technologies, environmentally friendly resources, local cultural practices and the principles of the "green economy". Particular attention is paid to creating added value for tourism markets through the integration of innovative approaches in the design, promotion and implementation of tourism products. The results of the study show that innovations not only contribute to the preservation of cultural and natural heritage, but also ensure increased competitiveness of tourism companies in the global market.